Overview of the Characteristics of Meningocele Patients at Dr. Kariadi General Hospital, Semarang, Indonesia - Aji Nawa Irawan Putro; Erie B. P. Setya Budi Andar (HM Publisher, 2023)
Background: Meningocele is a medical condition where there is a defect in the spinal area, which allows protrusion of cerebrospinal fluid through the defect. Although epidemiologically, this case is relatively small, given the potential for high morbidity and mortality caused by this disorder, it becomes urgent for further exploration regarding meningocele. This study aimed to provide a clinical picture of meningocele patients at Dr. Kariadi General Hospital, Semarang, Indonesia. Methods: This study was a descriptive observational study. A total of 12 meningocele patients participated in this study. Observation of clinical data and management of meningocele patients was carried out in this study. Univariate analysis was carried out with the help of SPSS software. Results: The mean age of the patients when they were first treated was 533 days, and the average age when they were first operated on was 191.5 days. Meningocele patients have an average hospital stay of 16.5 days. The majority of patients are male. The majority of meningocele patients have congenital limb anomalies. The majority of patients have a neural tube defect located in the lumbosacral region. The majority of meningocele patients have no infectious complications, and the majority receive VP-shunt placement. Conclusion: Meningocele patients at Dr. Kariadi General Hospital, Semarang, Indonesia, mostly have an overview of the location of neural tube defects in the lumbosacral region and have complications of limb anomaly.